O Grupo Sobrevento de teatro de formas animadas - Mantellatto, Alice Meira Bonfim [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Since prehistoric man seeks to dominate play scenes and images of their daily lives, to understand them or dominate. In the theater, the man tried to represent hunting scenes and deities. Since the first creation material representative of the gods, these objects acquire magical powers. After a long time, came the Puppet Theater, which through the use of various materials, the man concocted dolls in his image and likeness, as well as representations of animals. Subsequently, the Theater of Animated FormsVisual involved various props, like the mask, the shadow and the object. Thus, these elements can appear all together or not in the same show and are, therefore, the Theater of Animated Forms. How important human need to understand the world and events around them, the arts were needed to explain the divine and unreachable. Clumping the four languages of art: music, plastic arts, dance and theater, the Theater of Animated Forms of so characteristic of the man in search of the divine and sublime sentiments or not. In Brazil, faced with a multitude of excellent groups Theater of Animated Forms, the Sobrevento Group stands to monitor on an extensive repertoire theoretical foundation for the themes of the pieces created, and the high level of aesthetic sensitivity and artistic creation through is the dummies used in your repertoire. The objective of this study is to describe and analyze the Sobrevento Group considering the process of artistic creation, which led to the understanding of what is Theater of Visual Theater. To this end, guided interpretive anthropological approach, we conducted an ethnograph with the group

Desde a pré-história o homem busca dominar imagens e reproduzir cenas do seu cotidiano, seja para compreendê-las, seja para dominá-las. No teatro, o homem buscou representar cenas de caça e divindades. Desde a primeira criação material representante das divindades, esses objetos adquiriram poderes mágicos. Depois de um longo tempo, surgiu o Teatro de Bonecos, que por meio do uso de diversos materiais, o homem confeccionou bonecos à sua imagem e semelhança, bem como representações de animais. Posteriormente, o Teatro de Formas Animadas envolveu diversos elementos cênicos, como a máscara, a sombra e o objeto. Dessa forma, esses elementos podem aparecer todos unidos ou não num mesmo espetáculo, constituindo, portanto, o Teatro de Formas Animadas. Como importante necessidade do homem para compreender o mundo e os acontecimentos à sua volta, as artes foram necessárias para explicar o divino e o inalcançável. Aglutinando as quatro linguagens artísticas, ou seja, a Música, as Artes Plásticas, a Dança e o Teatro, o Teatro de Formas Animadas representa essa característica do homem em busca do divino e de sentimentos sublimes ou não. No Brasil, diante de uma infinidade de excelentes grupos de Teatro de Formas Animadas, o Grupo Sobrevento destaca-se por acompanhar em seu repertório um extenso fundamento teórico para os temas das peças criadas, além do alto nível estético e sensível de sua criação plástica através dos bonecos utilizados em seu repertório. O objetivo deste trabalho é descrever e analisar o Grupo Sobrevento considerando seu processo de criação artística, de maneira a compreender, em seus fundamentos, o Teatro de Formas Animadas. Para tanto, pautada numa abordagem antropológica interpretativista, foi realizada uma etnografia com o referido grupo
Keywords: Teatro de bonecos